High-Quality SnSe2 Single Crystals: Electronic and Thermoelectric Properties - Pham, Anh-Tuan; Vu, Thi Hoa; Cheng, Chang; Trinh, Thi Ly; Lee, Ji-Eun; Ryu, Hyejin; Hwang, Choongyu; Mo, Sung-Kwan; Kim, Jungdae; Zhao, Li-dong; Duong, Anh-Tuan; Cho, Sunglae (AMER CHEMICAL SOC, 2020)
High-quality SnSe2 single crystals were successfully synthesized using a temperature gradient method. N-type characteristics and strong anisotropic transport properties of SnSe2 single crystals were exhibited between the ab plane and the c-axis. At 673 K, the power factor (PF) value along the ab plane is 3.43 mu W cm(-1) K-2, while it is 0.92 mu W cm(-1) K-2 along the c-axis. The ratio between thermal conductivities along the ab plane (K, b ) and c-axis (kappa(c)) is on the order of 7.6 at 300 K, while this value is about 5.6 at 673 K. The thermoelectric figure of merit (ZT) in the c-axis (0.15) is higher than that (0.1) along the ab plane, according to the ultralow out-of-plane thermal conductivity. The electronic band structure results, which were examined by angle-resolved photoemission spectroscopy (ARPES) predicted the potential of improving the thermoelectric performance of SnSe 2 single crystals by electron doping.